UV-C and hydration state drive pulsed light-induced proteome damage in Bacillus pumilus spores - Dorbani, Imed; Armengaud, Jean; Carlin, Frédéric; Duport, Catherine (Frontiers in Microbiology, 2025)
IntroductionPulsed light (PL) is a non-thermal processing technology that inactivates microorganisms through high-intensity pulses of polychromatic light, including ultraviolet-C (UV-C). While the germicidal effect of PL has been widely studied, its impact on microbial proteomes remains poorly understood. Here, we investigate the proteomic response of Bacillus pumilus DSM492 (ATCC 27142) spores to PL treatment, comparing it to conventional UV-C 254 nm exposure.MethodsB. pumilus spores were either suspended in water or sprayed onto a polystyrene surface and exposed to PL or UV-C at fluences achieving a 5-log and a > 7-log reduction in viability. Proteomic changes were analyzed using mass spectrometry to identify proteins with decreased abundance after treatment.ResultsPL treatment induced a significantly greater proteomic alteration compared to UV-C, particularly in spores suspended in water, where the number of proteins with decreased abundance was ~6-fold higher than in spores sprayed on a polystyrene surface. Proteomic analysis revealed that the effect of PL in water was primarily due to UV-C 254 nm, whereas on polystyrene, UV-C 254 nm had no significant impact. Furthermore, proteins most affected by PL were enriched in photosensitive amino acids such as tryptophan, histidine, tyrosine, cysteine, and methionine, suggesting oxidation and photoreactivity as key degradation mechanisms.DiscussionAlthough the overall inactivation rate could not be directly correlated with proteome damage, we identified that core proteins involved in DNA and RNA protection and repair were specifically targeted by PL. These findings provide new insights into the molecular mechanisms underlying PL-mediated microbial inactivation and highlight the role of protein photodamage in spore susceptibility.